Letter from Kasimir Fajans to Marianne and Max Bredig, April 1944 - Fajans, Kasimir (1944)
Kasimir Fajans (1887-1975) expresses his condolences to Marianne Homburger (1903-1986) and Max Albert Bredig (1902-1977) upon the death of their father, Georg Bredig (1868-1944).
Keywords: Fajans, Kasimir, 1887-1975; Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Bredig, Georg, 1868-1944; Condolence notes